Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Southwest)--Crangonid shrimp - Siegfried, Clifford .A (U.S. Departement of the Interior, 1989)
U.S. Fish Wildl. Serv. Biol. Rep. 82(11.125)